Pendekatan Kontekstual dalam Pembelajaran Pendidikan Agama Islam melalui Metode Karyawisata: Studi Kasus di SD Kyai Abdulallah Ubaid II Surabaya - Zainudin Fahmi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study applies a descriptive qualitative approach with data gathered through observation, interviews, and documentation. It aims to outline the planning and execution of a contextual approach in learning Islamic religious education by applying the field trip method and examining outcomes prior to and after its use to Islamic religious education learning at SD Kyai Abdullah Ubaid II Surabaya. Strategy of contextual method was selected since it can link learning material’s of Islamic religious education with real experiences, so that students can understand religious values ​​in a more applicable way. The subjects of this research include PAI teachers, class IV students and school principals. Data analysis employed the Miles and Huberman framework, covering reduction, presentation, and inference. The study of result shows that Islamic religious education teacher’s at Kyai Abdullah Ubaid II Elementary School have implemented a strategy of contextual approach effectively, particularly through Islamic religious education learning activities based on students' real-life experiences. This approach was implemented through planned field trips, such as practicing the dhuha prayer’s at the Ya'qub Mosque. A contextual approach combined with a field trip method has been proven to increase the enthusiasm and engagement of fourth-grade students at Kyai Abdullah Ubaid II Elementary School, Surabaya. They demonstrated a better understanding in the context of Islamic education learning, and the PAI teacher’s helped students understand Islamic values in a practical way by inviting fourth-grade students to perform ablution before practicing the Dhuha prayer during PAI learning at the Ya'qub Mosque.